The The Effect of Current Ratio, Debt To Equity Ratio and Return On Assets on Company Value - Ricky Agusiady; Adelia Rahmawati; Aryanti Ratnawati; Muhammad Taofik Ismail; Indri Gustirani; Henny Setyo Lestari (International Journal of Islamic Business and Management Review, 2024)
Company value is important for a company, because before investing, investors will conduct a survey first, one of which is to look at the development of the company's value. Automotive companies and their components listed on the IDX in 2017-2021 had unstable growth, as seen during the Covid 19 pandemic, the company value of these companies fluctuated and even predominantly decreased. Many factors can effects company value. Therefore, the aim of this research is to find out, explain and describe the effect of the Current Ratio, Debt to Equity Ratio and Return on Assets on the Value of Automotive Sub-Sector Companies and Their Components Listed on the Indonesia Stock Exchange for the 2017-202 period. This study uses a quantitative approach. The population in this study was 15. The sampling technique in this study used a purposive sampling technique, so that a sample of 8 companies was obtained. The data analysis method in this research uses multiple regression tests because there is more than one independent variable that effectss the dependent variable. Data processing in this research uses Eviews version 9. The results obtained in this research are that the Current Ratio, Debt to Equity Ratio and Return On Assets partially have a significant effect on company value (Tobin's Q). Simultaneously the Current Ratio, Debt to Equity Ratio and Return On Assets obtained results that simultaneously had a significant effect on company value (Tobin's Q). The most recent of this research is the period of increasing years.